Experimental study of the static behaviour of the PEM fuel cell - Nedjem Eddine Benchouia; Bouziane Mahmah (IPCO, 2017)
This work proposes and justifies an easy electric model of a power generation system based on a PEM fuel cell, the H-Tec PEM Power Module of 1.2W. This model has been developed by means of experimental data obtained in our laboratory.